Ranging pattern development of a declining delphinid population: A potential cascade effect of vessel activities. (15th March 2023) - Lin, Wenzhi; Zheng, Ruiqiang; Liu, Binshuai; Chen, Shenglan; Lin, Mingli; Serres, Agathe; Liu, Mingming; Liu, Wenhua; Li, Songhai
Abstract: It is generally accepted that vessel activity causes various behavioral responses of cetaceans and undermines individual fitness. Whether or how it can lead to a demographic response of populations remains rarely examined. In the northern Beibu Gulf, China, vessel activities have sharply increased in the past two decades, while abnormal demographic dynamics was recently noted for the resident Indo-Pacific humpback dolphins. The present study first examined the humpback dolphins' utilization distribution (UD) from 2003 to 2019. Habitat suitability was then modeled with the sighting data collected before the most recent population reduction. Finally, we tried to disentangle the anthropogenic driver of dolphin demography by cross-referring the spatiotemporal development of dolphins' UD, vessel activities, and habitat suitability. Our results showed that the dolphins' UD shrank substantially during the port expansion in the early 2010s, and we suggest that the consequential increase in vessel activities might impose extra marine stressors on the resident humpback dolphins. To reduce the boat interaction, the dolphins steadily shifted their core area to a less suitable area in the east during 2015–2017, when unnaturally low survivals were recorded. Afterward, the dolphin core area partially shifted back to the more suitable area in the west, which corresponded to the improving dolphin survival in 2018. Our finding suggested that the vessel activity may be responsible for the dolphin displacement, while staying in the less suitable area may further lead to a more severe and acute demographic consequence on the population. The underlying and indirect impact of vessel activities as disclosed by the present study is particularly important for port management, marine planning, and conservation practice regarding coastal cetaceans, especially for those resident and endangered populations inhabiting the urbanized coastal areas. Highlights: Core area of dolphin shifted to un-preferred region when low survivals were recorded. Segregated distributions between vessel and dolphins were observed. Dolphin core area recently shift back to suitable region with recovering survival. Vessel cause dolphin displacement, which in turn compromise the population fitness. Dolphin ranging pattern reflect trade-off between vessel interaction and habitat quality.